Reliable relay assisted wireless multicast using network coding - Pingyi Fan; Chen Zhi; Chen Wei; Ben Letaief, K. (IEEE journal on selected areas in communications, 2009)
We first consider a topology consisting of one source, two destinations and one relay. For such a topology, it is shown that a network coding based cooperative (NCBC) multicast scheme can achieve a diversity order of two. In this paper, we discuss and analyze NCBC in a systematic way as well as compare its performance with two other multicast protocols. The throughput, delay and queue length for each protocol are evaluated. In addition, we present an optimal scheme to maximize throughput subject to delay and queue length constraints. Numerical results will demonstrate that network coding can bring significant gains in terms of throughput.